Conservative Management of Spondylodiscitis after Laparoscopic Sacral Colpopexy: A Case Report and Review of Literature - Tavares, Madalena Andrade; Silva, Ana Rita; Melo, Marta Gomes de; Pacheco, Márcia; Coutinho, Nuno; Ambrósio, Alexandre; Tapadinhas, Paula (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Sacral colpopexy is one of the standard procedures to treat apical pelvic organ prolapse. In most cases, a synthetic mesh is used to facilitate the colposuspension. Spondylodiscitis is a rare but potentially serious complication that must be promptly diagnosed and treated, despite the lack of consensus in the management of this complication. We report one case of spondylodiscitis after a laparoscopic supracervical hysterectomy and sacral colpopexy treated conservatively. We also present a literature review regarding this rare complication. A conservative approach without mesh removal may be possible in selected patients (stable, with no vaginal lesions, mesh exposure or severe neurologic compromise). Hemocultures and culture of image-guided biopsies should be performed to direct antibiotic therapy. Conservative versus surgical treatment should be regularly weighted depending on clinical and analytical progression. A multidisciplinary team is of paramount importance in the follow-up of these patients.
Keywords: spondylodiscitis; sacral colpopexy; pelvic organ prolapse; urogynecological mesh; discitis